2022
DOI: 10.1021/acssuschemeng.1c07332
|View full text |Cite
|
Sign up to set email alerts
|

How Does Surface Charge Engineering of Bacillus subtilis Lipase A Improve Ionic Liquid Resistance? Lessons Learned from Molecular Dynamics Simulations

Abstract: Biocatalysis in ionic liquids (ILs) gained substantial interest due to solvent properties of the ILs, such as near-zero vapor pressure, high thermal stability, and wide tunability. Enzymes are often not catalytically active in ILs; therefore, understanding and improving enzyme resistance in ILs are essential to enable efficient biocatalysis in ionic liquids. Surface charge engineering has repeatedly been reported to enhance enzyme resistance toward ILs. However, the molecular knowledge about how substitutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…The BMIM + cation topology was obtained using the ATB online server with the GROMOS96 54a7 force field based on previous reports. ,,, Due to the PDB2PQR server’s speed and accuracy compared to other methods, protonation states were assigned based on predicted p K a utilizing the PROPKA technique at pH 7.4 . The protonation state of catalytic residues such as H156 was assigned with respect to previous studies using pdb2gmx. ,, The simulation parameters such as box size (cubic, 10 Å from the box edge), SPC/E water model, , system ionization, , neutralization, energy minimization, and NVT and NPT ensembles follow our previous study with a time step of 2 fs . The 100 ns production run was carried out with three independent runs using the NPT ensemble (2 fs time step at 300 K) as previously reported .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMIM + cation topology was obtained using the ATB online server with the GROMOS96 54a7 force field based on previous reports. ,,, Due to the PDB2PQR server’s speed and accuracy compared to other methods, protonation states were assigned based on predicted p K a utilizing the PROPKA technique at pH 7.4 . The protonation state of catalytic residues such as H156 was assigned with respect to previous studies using pdb2gmx. ,, The simulation parameters such as box size (cubic, 10 Å from the box edge), SPC/E water model, , system ionization, , neutralization, energy minimization, and NVT and NPT ensembles follow our previous study with a time step of 2 fs . The 100 ns production run was carried out with three independent runs using the NPT ensemble (2 fs time step at 300 K) as previously reported .…”
Section: Methodsmentioning
confidence: 99%
“…The main conclusion revealed that up to 13% of substitutions have improved resistance, providing a desirable source for fully understanding the protein–IL interaction. Meanwhile, the BSLA–SSM library holds more promise of unmasking the general design principle(s) than the traditional directed evolution campaign, as relatively few amino acid substitutions have been studied in comparison to the diversity that nature provides. , In our prior work, we successfully used atomistic MD simulation to explore dynamic interactions of ILs and enzyme variants at site resolution. ,, However, a large-scale statistical exploration based on more variants in multiple ILs is required to print a comprehensive landscape.…”
Section: Introductionmentioning
confidence: 99%
“…77,87 Further, MD simulations have shown surface charge and surface polar engineering to be successful strategies to enhance the IL/ polar solvent tolerance of a lipase. 88,89 Pramanik et al also demonstrated that the reduction in the interaction between the IL cation and the LipA surface is an efficient approach to stabilize LipA in a binary mixture of IL and water. 83,88 In the PS-IL forms, the surfactant layer in SFPLs imparts IL tolerance to the protein by lowering the concentration of both the cation and anion of IL in the vicinity of the protein surface, i.e., by screening the protein-IL interactions (refer to Fig.…”
Section: Ionic Liquid Tolerancementioning
confidence: 99%
“…88,89 Pramanik et al also demonstrated that the reduction in the interaction between the IL cation and the LipA surface is an efficient approach to stabilize LipA in a binary mixture of IL and water. 83,88 In the PS-IL forms, the surfactant layer in SFPLs imparts IL tolerance to the protein by lowering the concentration of both the cation and anion of IL in the vicinity of the protein surface, i.e., by screening the protein-IL interactions (refer to Fig. 4 and Table S5, ESI †).…”
Section: Ionic Liquid Tolerancementioning
confidence: 99%
See 1 more Smart Citation